2010
DOI: 10.1021/jp106530h
|View full text |Cite
|
Sign up to set email alerts
|

Fold Catastrophes and the Dependence of Free-Energy Barriers to Conformational Transitions on Applied Force

Abstract: Applied mechanical force (f) can activate conformational change in molecules by reducing the height of a free-energy barrier (DeltaG(b)). In this paper, molecular dynamics simulations are carried out with umbrella sampling and self-consistent histogram methods to determine free-energy profiles for a coarse-grained model of a protein under an applied force. Applied force is shown to cause fold catastrophes, where free-energy minima are destabilized until they disappear. It is well-known that a fold catastrophe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…A need to account for the ductile regime has emerged also from earlier theoretical and molecular simulation studies of protein unfolding. Stretching forces required to destabilize some folded states were thermodynamically larger than previously expected (32), and both all-atom and coarse-grained simulations showed a nonlinear dependence of the activation barrier on force, indicative of kinetically ductile behavior (33)(34)(35).…”
Section: Discussionmentioning
confidence: 73%
“…A need to account for the ductile regime has emerged also from earlier theoretical and molecular simulation studies of protein unfolding. Stretching forces required to destabilize some folded states were thermodynamically larger than previously expected (32), and both all-atom and coarse-grained simulations showed a nonlinear dependence of the activation barrier on force, indicative of kinetically ductile behavior (33)(34)(35).…”
Section: Discussionmentioning
confidence: 73%
“…The findings of the later studies [38][39][40][41] agree with Garg [36] in that the applied force ( f ) modifies the energy barrier as ~ (1-f/f c ) 1.5 , where f c is the critical force of detachment. Recently, such a scaling has been verified in molecular dynamics simulations as well [42,43]. The finding of Lacks et al [42] is particularly interesting in that they showed that it is not only the energy barrier, but also the free energy barrier that follows the scaling of ~(1-f/f c ) 1.5 .…”
Section: Introductionmentioning
confidence: 86%
“…Recently, such a scaling has been verified in molecular dynamics simulations as well [42,43]. The finding of Lacks et al [42] is particularly interesting in that they showed that it is not only the energy barrier, but also the free energy barrier that follows the scaling of ~(1-f/f c ) 1.5 . In the light of these previous studies, we write the overall frequency of rupture of a soft sphere from a solid substrate (assuming a linear friction) as follows:…”
Section: Introductionmentioning
confidence: 86%
“…Near the critical force, it can be shown that the barrier vanishes as |F − F c | 3/2 , this behavior being universal and independent of detailed molecular properties. [45][46][47][48] More specifically (see Appendix B), the transition rate can be approximated by…”
Section: ′′mentioning
confidence: 99%
“…Although, strictly speaking, these results hold only in the vicinity of the critical force F c , simulations suggest that the catastrophe theory predictions often remain accurate even far away from the catastrophe point. 45,48,49,87 Combined with the easier accessibility of the high force regime, these arguments suggest that most experimental studies happen to be on the Hammond part of the reaction path, which is well described by the one-dimensional cubic parabola model. This may further explain the wide success of the cubic parabola model in interpreting singlemolecule data.…”
Section: If One-dimensional Models Fail Why Do They Fit Experimementioning
confidence: 99%